MRI Case Report of Perianal Fistula with T2 TSE SPIR Sequence - Apriantoro, Nursama Heru; Saleh, Arif Rohman; Sari, Gando; Supriyono, Puji; Widiatmoko , Mahfud Edy (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
MRI is a diagnostic imaging tool crucial for pelvic examination in perianal fistula cases. MRI imaging offers some advantages, especially in showing the area of spesi and secondary dilatation. Both have a high recurrence rate after surgery and an important role in determining surgical outcomes and minimizing complications. This study aims to evaluate pelvic MRI examination of perianal fistulas using the T2 TSE SPIR (Turbo Spin Echo Spectral Presaturation with Inversion Recovery) sequence. Research design used a qualitative descriptive method with participatory observation through a case study approach to Perianal Fistula using T2 TSE_SPIR. It was carried out at the Radiology Department of Mayapada Hospital in South Jakarta from August to December 2022. The MRI equipment Philips Achieva 1.5 Tesla with Sense Body Coil. MRI contrast agent of gadoteric acid, Vitamin E capsule, was attached to the perianal fistula location to make it easier for the radiologist to see the path of the perianal fistula. The results of Pelvis MRI images in perianal fistulas using the T2 TSE SPIR sequence shown with clear boundaries of perianal fistulas with anal organs, sigmoid colon, bladder, and prostate between one organ and another. Implementing the selection of the T2 TSE SPIR sequence to visualize fluid images becomes hyper-intensive by suppressing fat signals so that only fluid is visible in the perianal abscess and fistula images.